Contemporary insights and prospects on ferroptosis in rheumatoid arthritis management - Zhao, Hongyu; Dong, Qiumei; Hua, Hao; Wu, Hao; Ao, Limei (Frontiers in Immunology, 2024)
Rheumatoid arthritis (RA) is a common autoimmune disease characterized primarily by persistent synovial inflammation and joint destruction. In recent years, ferroptosis, as a novel form of cell death, has garnered widespread attention due to its critical role in various diseases. This review explores the potential mechanisms of ferroptosis in RA and its relationship with the pathogenesis of RA, systematically analyzing the regulatory role of ferroptosis in synovial cells, chondrocytes, and immune cells. We emphasize the evaluation of ferroptosis-related pathways and their potential as therapeutic targets, including the development and application of inhibitors and activators. Although ferroptosis shows some promise in RA treatment, its dual role and safety issues in clinical application still require in-depth study. Future research should focus on elucidating the specific mechanisms of ferroptosis in RA pathology and developing more effective and safer therapeutic strategies to provide new treatment options for RA patients.